The Study of 'Don't Hug Me I'm Scared' Web Series Storytelling For IP Design Regarding Safe Viewing Content For Children - Ilona Matakupan, Nikita (Bina Nusantara University, 2023)
In 2022 the internet was getting more advanced, and every age can use it. For a long time, the mass media has become a tool used in children's socialization. The easiest way to teach children is via the internet, specifically through child-friendly shows. The shows are usually educational, such as learning about colors, letters, numbers, social teachings, etc. They can imitate or learn the teachings they watch in everyday life. This children's content has positive and negative impacts, but one of the problems is the delivery of indecent content such as violence, pornography, or wrong teachings inserted into the spectacle. Apart from problems with YouTube's algorithm, irresponsible adults make children who watch it participate in acts of violence or are traumatized by watching it. This does not mean that all children's viewing of content is terrible, but that there needs to be discretion and initiative on the part of parents. This case could create a big scandal in the internet world. This research aims to dissect and analyze a well-known web series on YouTube, 'Don't Hug Me I'm Scared' by Joseph Pelling, Baker Terry, and Rebecca Sloan, in terms of storytelling and create an Intellectual Property (IP) to create safe content for children. One of the theories circulating about this animation is the problem of children's content being deviated due to the actions of adults and their criticism, making this series suitable as the main foundation for research.